Evaluasi Kepuasan Pengguna Electronic Health Record (EHR) Menggunakan Metode EUCS (End User Computing Satisfaction) di Unit Rekam Medis Pusat RSUPN Dr. Cipto Mangunkusumo - Gamasiano Alfiansyah; Andar Sifa’il Fajeri; Maya Weka Santi; Selvia Juwita Swari (FORIKES, 2020)
RSUPN Dr. Cipto Mangunkusumo is one of the hospitals whose services have used Electronic Health Record (EHR). The implementation of EHR is frequent loading and errors during service and lacking for several menus. The research purpose was to evaluate user satisfaction related to reporting on the Electronic Health Record (EHR) in the central medical records unit Dr. RSUPN. Cipto Mangunkusumo. This research was quantitative descriptive with population of all Electronic Health Record users in the central medical record unit, with 50 sample of respondents. The sampling technique was conducted by sistematic random sampling. Data was analyzed through scoring and presented in table form. The results showed that the dimension of accuracy was 73.28%, format was 71.6%, ease of use was 69.2%, content was 69.2 %, and timelines was 65.66%. These dimension scores indicated good criteria or the user was satisfied with the current Electronic Health Record (EHR) condition, but it requires the development of information systems by adding and adjusting modules contained in the EHR so that user satisfaction continues to increase. Keywords: evaluation; electronic health record (HER); end user computing satisfaction (EUCS) ABSTRAK Rumah Sakit Umum Pusat Nasional (RSUPN) Dr. Cipto Mangunkusumo merupakan salah satu rumah sakit yang pelayanannya sudah menggunakan SIMRS yang disebut Electronic Health Record (EHR). Penggunaan EHR sering loading dan error pada saat pelayanan dan ada beberapa menu yang masih kurang. Tujuan penelitian ini adalah untuk mengevaluasi kepuasan pengguna terkait pelaporan pada Electronic Health Record (EHR) di unit rekam medis pusat RSUPN Dr. Cipto Mangunkusumo. Penelitian ini adalah kuantitatif deskriptif dengan populasi seluruh pengguna Electronic Health Record di unit rekam medis pusat, dan sampel berjumlah 50 responden. Teknik pengambilan sampel dilakukan dengan sistematic random sampling. Analisa data dilakukan melalui skoring dan disajika ndalam bentuk tabel. Hasil penelitian menunjukkan bahwa dimensi keakuratan memiliki nilai tertinggi, yaitu 73,28%, tampilan 71,6%, kemudahan pengguna 69,2%, isi 69,2%, dan waktu 65,66%. Skor dalam dimensi tersebut termasuk dalam kriteria baik atau pengguna puas terhadap konsisi Electronic Health Record (EHR) saat ini, namun masih diperlukan pengembangan sistem informasi serta menambahkan dan menyesuaikan modul yang ada di dalam EHR sehingga kepuasan pengguna terus meningkat. Kata kunci: evaluasi; electronic health record (HER); end user computing satisfaction (EUCS)